Extra pelvic endometriosis: Retrospective analysis on 200 cases in two different countries. (October 2017) - Matalliotakis, Michail; Goulielmos, George N.; Kalogiannidis, Ioannis; Koumantakis, Georgios; Matalliotakis, Ioannis; Arici, Aydin
Abstract: Objective(s): The purpose of the study was to review patients' characteristics and the location of extrapelvic endometriosis. Study design: Out of 1000 women with endometriosis during a 20 year period, we found 200 cases with extra pelvic endometriosis. Medical reports were evaluated and the diagnosis was confirmed on the pathological specimen. This study involved cases from two different geographical areas, New Haven and Crete. The age, parity, symptoms, previous surgeries, diagnostic modalities, histopathological evaluation and location of endometriotic implants found in other areas were recorded and analyzed from the patient's charts. Main outcome measure(s): Statistical methods included x 2 and Mann-Whitney U test s measuring incidence of right-VS left sided endometriosis. Results: 200 patients with extrapelvic endometriosis and 800 patients with pelvic endometriosis were included in the study. The gastrointestinal tract represents the most common location of extrapelvic endometriosis with 104/200(52%) cases (p < 0, 01), followed by the urinary system with70/200(35%) cases. We observed the Left-sided ureter being involved in 49/200(24, 5%) cases, significantly higher compare with the right-sided ureter 21/100(10, 5%) (p < 0, 01). All women had similar characteristics involving age, weight, main complaints, age of menarche, endometriosis stages, gravid and family history of endometriosis. Conclusion(s): The gastrointestinal tract and the urinary system are the most common sites of the extrapelvic endometriosis, which was obvious in both countries. Moreover, we observed that there are no significant differences in demographic variants, menstrual and reproductive characteristics in women with extrapelvic and pelvic endometriosis.